Emotional Regulation Ability in Early Childhood: Role of Coparenting and Mindful Parenting - Mafaza Mafaza; Septi Mayang Sarry (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
Most of the demands and tasks necessary during the development of early childhood center around children’s emotional regulation ability. At this time, parents have an important role in socializing the emotional development to children during parenting practices. This study aimed to determine the role of mindful parenting and coparenting competence simultaneously towards emotional regulation ability in early childhood. 370 parents of children in early childhood participated in this study (173 fathers and 197 mothers) chosen using a purposive sampling method. Parents completed the emotional regulation skill questionnaire, Bangor mindful parenting scale, and coparenting competence scale. The results of multiple linear regression analysis indicated that mindful parenting and coparenting competence have a significant role in predicting children’s emotional regulation competence simultaneously (R2 = 0.121, F (2.369) = 23.01, p < .001). This indicates that improving children’s emotional regulation ability in early childhood is related to the children’s internal factors and the ability of parents to carry out parenting practices and form a good family emotional climate.